2017
DOI: 10.1002/pssa.201700857
|View full text |Cite
|
Sign up to set email alerts
|

Width‐Dependent Sheet Resistance of Nanometer‐Wide Si Fins as Measured with Micro Four‐Point Probe

Abstract: This paper extends the applicability of the micro four-point probe technique from the sheet resistance measurements on large areas toward narrow (<20 nm) semiconducting nanostructures with an elongated fin geometry. Using this technology, it is shown that the sheet resistance of boron-implanted and laser-annealed silicon fins with widths ranging from 500 down to 20 nm rises as the width is reduced. Drift-diffusion simulations show that the observed increase can be partially explained by the carrier depletion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Before discussing the electrical contact between the μ4pp electrodes and an individual fin, a general description of a μ4pp measurement on large blanket semiconducting samples is needed. The μ4pp electrodes comprise four Ni-coated Si cantilevers with a spacing of 8 µm and a contact size d contact ≈ 300 nm [ 6 , 9 10 ]. In a μ4pp measurement, the electrodes are landed on the sample surface after which a current I in is injected into the investigated sample via two of the electrodes while the induced voltage drop V is measured between the other two electrodes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before discussing the electrical contact between the μ4pp electrodes and an individual fin, a general description of a μ4pp measurement on large blanket semiconducting samples is needed. The μ4pp electrodes comprise four Ni-coated Si cantilevers with a spacing of 8 µm and a contact size d contact ≈ 300 nm [ 6 , 9 10 ]. In a μ4pp measurement, the electrodes are landed on the sample surface after which a current I in is injected into the investigated sample via two of the electrodes while the induced voltage drop V is measured between the other two electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…The transition from planar to three-dimensional transistor architectures such as the fin field-effect transistor (finFET) [ 1 ] has raised the need for measuring the electrical properties of nanometer-wide conducting features [ 2 ]. Recently, it has been shown that the micro four-point probe (μ4pp) technique, which is commonly used for sheet resistance measurements on blanket materials or relatively large pads (larger than 80 × 80 µm 2 ) [ 3 5 ], provides a solution to this requirement [ 6 ]. The μ4pp technique was demonstrated to provide (sheet) resistance measurements in single fins without the need for dedicated Kelvin resistor or transmission line structures [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the measurement of R 1 and R 2 is done using the extra two electrodes 3 and 4 (not shown in Figure a) of our microprobes after forming the corrrespoding electrical contacts R 3 and R 4 with a high current (>500 μA; Figure b) to ensure a low contact resistance (i.e., R 3 , R 4 << R 1 , R 2 ). Here, because the Si sample is highly doped, R sample is much lower than the contact resistances (i.e., R sample << R 1 , R 2 , R 3 , R 4 ) and can thus be neglected, making that all contact resistances can be obtained using a series of independent two‐point measurements. For example, R 1 is extracted using R 1 = 0.5 × ( R 1–3 + R 1–4 − R 3–4 ), where R 1–3 is the two‐point measurements between electrodes 1 and 3.…”
Section: The Electrical Contacting Processmentioning
confidence: 99%
“…Ever since the transition from planar to 3D transistor architectures such as the fin field‐effect transistor (finFET), there has been a rising need for metrology solutions able to measure the electrical properties of nanometer‐wide conducting features . Recently, it has been shown that the micro four‐point probe (μ4pp) technique is able to measure the resistance in nanometer‐wide fins . To perform such measurements with a high precision, all four electrodes are required to form low‐resistance contacts with the sample under investigation .…”
Section: Introductionmentioning
confidence: 99%